2009
DOI: 10.1007/s12192-008-0077-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of orchardgrass p23, a flowering plant Hsp90 cohort protein

Abstract: p23 is a heat shock protein 90 (Hsp90) cochaperone and stabilizes the Hsp90 heterocomplex in mammals and yeast. In this study, we isolated a complementary DNA (cDNA) encoding p23 from orchardgrass (Dgp23) and characterized its functional roles under conditions of thermal stress. Dgp23 is a 911 bp cDNA with an open reading frame predicted to encode a 180 amino acid protein. Northern analysis showed that expression of Dgp23 transcripts was heat inducible. Dgp23 has a well-conserved p23 domain and interacted with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Purified Arabidopsis mitochondrial MDH (EC 1.1.1.37) 68 and purified recombinant wild-type and mutant YUC6 proteins at the indicated molar ratios were incubated in 40 mM HEPES (pH 7.5) buffer at 45 °C. The absorbance at 340 nm, indicating aggregation of MDH, was monitored for 30 min using a Beckman DU-800 spectrophotometer (Beckman Coulter) attached to a thermostatic cell holder assembly 58 60 68 .…”
Section: Methodsmentioning
confidence: 99%
“…Purified Arabidopsis mitochondrial MDH (EC 1.1.1.37) 68 and purified recombinant wild-type and mutant YUC6 proteins at the indicated molar ratios were incubated in 40 mM HEPES (pH 7.5) buffer at 45 °C. The absorbance at 340 nm, indicating aggregation of MDH, was monitored for 30 min using a Beckman DU-800 spectrophotometer (Beckman Coulter) attached to a thermostatic cell holder assembly 58 60 68 .…”
Section: Methodsmentioning
confidence: 99%
“…The HSP20-like chaperone is highly homologous to an HSP20-like chaperone from clover ( Medicago truncatula ) that contains the p23 domain. As p23 is one of the cochaperones of HSP90 and stabilizes the HSP90 heterocomplex [ 98 , 99 ], enhanced expression of this chaperone gene under heat stress also indicated that upregulation of HSP90-related proteins are important for heat tolerance in perennial grasses, as discussed above in the proteomic study. In another study, using the sequence of the HSP70 gene isolated by SSH in A. scabra and the reported sequence of a sHSP ( HSP16 ) gene in A. stolonifera , the expression levels of the two genes were compared between heat-sensitive A. stolonifera and thermal A. scabra (Huang, unpublished data).…”
Section: Identification and Characterization Of Hsps Associated Wimentioning
confidence: 99%
“…Deletion studies suggest that human and yeast p23 interacts with both the N-terminal and middle domains of Hsp90␤ in vitro (McLaughlin et al, 2006), whereas plant p23 is not like human and yeast p23, interacting with cytosolic Hsp90 (Krishna and Zhang, 2003). However, in a recent study, it was shown that p23 from orchardgrass could interact with DgHsp90, which is a Hsp90 homolog in orchardgrass located in the ER (Cha et al, 2009). In this study, organellar and cytosolic AtHsp90s showed different interactions with the tested cofactors, cpHsp70, Hsp70, Hsp70t-2, Cyp40, p23 and a substrate protein of NOS, organellar AtHsp90s could interact with most of the tested cofactors, while cytosolic AtHsp90s could not interact with these cofactors (Fig.…”
Section: Discussionmentioning
confidence: 52%